Parameters Reduction Comparisions - Mohammed, Mohammed Adam Taheir; Wan Maseri, Wan Mohd; Ruzaini, Abdullah Arshah; Liu, Yao (Asian Academic Research Associates, 2014)
In this proposal testing techniques has been done based on calculating reduction of optimal and sub optimal parameters for decision making soft set theory. Previous techniques of reduction in decision making for a Boolean-valued information system of standard soft set are described. Hybrid reduction compared to Maji, Chen, and Kong shows best criterion for parameters reductions on the conclusion part